An empirical analysis of UK imports: Is there evidence of hysteresis? - Emilia Penkova (Universität Dortmund, Wirtschafts- und Sozialwissenschaftliche Fakultät, 2005)
The paper re-examines the validity of the hysteresis hypothesis by applying it to the UK import volume from the world's five largest economies: Germany, France, Italy, Japan and the USA, over the period 1975 to 1994. Disaggregated bilateral data (4-digit ISIC) are used and hysteresis is captured by dummy variable which is an extension of work by Parsley and Wei (1993). Panel estimation is undertaken and the Seemingly Unrelated Regression (SUR) technique is employed. There is evidence that hysteresis appears important for UK imports and varies across industries and countries.
Keywords: C23; F14; 330